The relationship between school climate and teachers commitment among primary teacher's in Sri Aman, Sarawak / Camellia Othman - Othman, Camellia (2014)
School climate has been a subject of interest to educators and researchers for over a century. As early as 1908, Perry was the first to explore the impact of school climate on student learning (Cohen & Geier, 2010).The purpose of the study is to investigate the relationship between school climate and teachers' commitment. The study also examined to investigate the assumption and predictability of key dimensions of school climate in relation to Achievement Press, Teacher Professionalism, Collegial Leadership, and Institutional Vulnerability towards teacher commitment. This study also explored the relationships of school climate and the organizational commitment of teachers from primary school in the district of Sri Aman in Sarawak. The population of this study involved of teachers from five National Primary Schools in the Sri Aman district with 131 respondents has been selected as a sample. Data was collected by using the quantitative method. Two instruments was used; (1) Organisational Climate Index (OCI) by Hoy, Smith and Sweetland (2003) and (2) Organizational Commitment Questionnaire (OCQ) by Cevat Celep (2000). The dependent variable was teacher commitment was measured by the 12 items and independent variable was measured by the 30 items of the organizational climate. The quantitative data was analysed using the Statistical Package for Social Sciences (SPSS) Version 21.0. Descriptive statistics and inferential statistic was used to address the objective of the study. The result showed that the level of school climate and teachers' commitment of the selected five National Primary Schools is in the moderate level. As a result for the correlation between school climate dimensions, it was determined that they were positively correlated with the teachers' commitment. The regression analysis was shows that only Achievement Press made a significant contribution to teachers' commitment.